Abundantly expressed class of noncoding RNAs conserved through the multicellular evolution of dictyostelid social amoebas - Kjellin, Jonas; Avesson, Lotta; Reimegård, Johan; Liao, Zhen; Eichinger, Ludwig; Noegel, Angelika; Glöckner, Gernot; Schaap, Pauline; Söderbom, Fredrik (Genome Research, 2021)
Aggregative multicellularity has evolved multiple times in diverse groups of eukaryotes, exemplified by the well-studied development of dictyostelid social amoebas, for example, Dictyostelium discoideum. However, it is still poorly understood why multicellularity emerged in these amoebas while the majority of other members of Amoebozoa are unicellular. Previously, a novel type of noncoding RNA, Class I RNAs, was identified in D. discoideum and shown to be important for normal multicellular development. Here, we investigated Class I RNA evolution and its connection to multicellular development. We identified a large number of new Class I RNA genes by constructing a covariance model combined with a scoring system based on conserved upstream sequences. Multiple genes were predicted in representatives of each major group of Dictyostelia and expression analysis confirmed that our search approach identifies expressed Class I RNA genes with high accuracy and sensitivity and that the RNAs are developmentally regulated. Further studies showed that Class I RNAs are ubiquitous in Dictyostelia and share highly conserved structure and sequence motifs. In addition, Class I RNA genes appear to be unique to dictyostelid social amoebas because they could not be identified in outgroup genomes, including their closest known relatives. Our results show that Class I RNA is an ancient class of ncRNAs, likely to have been present in the last common ancestor of Dictyostelia dating back at least 600 million years. Based on previous functional analyses and the presented evolutionary investigation, we hypothesize that Class I RNAs were involved in evolution of multicellularity in Dictyostelia.